The Effect of Service Quality and Clinic Image on Satisfaction to Mediate Revisit Intention and Loyalty in Beauty Clinic Industry - Andrew Lienata; Margaretha Pink Berlianto (PT Mattawang Mediatama Solution, 2023)
The aesthetic sector of healthcare services has grown significantly for both men and women in Indonesia and around the world. This study targets to examine the direct effect of service quality, which consists of tangibility, reliability, responsiveness, assurance, empathy, and clinic image, on patient satisfaction, which is assessed by the expectation of intention to revisit and patient loyalty. A questionnaire was used to collect data for this quantitative analysis. The research focused on patients who had received aesthetic treatment at SKYN Clinic in South Jakarta, Indonesia. According to data, there were 4,290 outpatients between January and August of 2022. It was determined that there were a total of 231 samples. The sampling technique used was systematic sampling. The research study utilized SEM-PLS (Partial Least Square-Structural Equation Modeling). Patient satisfaction positively influenced patient loyalty and revisit intention, while service quality and clinic image positively influenced patient satisfaction. This study revealed that to compete with the competitors in the beauty clinic industry, revisit intention and patient loyalty must be strengthened. Practitioners in the business of aesthetics, is required to rise customer satisfaction by promoting healthcare service quality factors and the overall clinic image.